The Influence of Bank Risk and Bank Internal Factors on Stock Prices in the Indonesian Banking Industry - Prakoso, Sasmito W. Rico; Wijaya W, Richy; Zulfiqar, Faisal Labib (Indonesian Journal Publisher, 2024)
This study examines the influence of risk and internal bank factors on banking companies listed on the Indonesia Stock Exchange. Banking risk is measured by Non-Performing Loans, while internal bank factors such as Book to Market Ratio, Return on Equity, Price/Earnings to Growth Ratio, Debt to Equity Ratio, Earnings per Share, Bank Size, and Institutional Ownership Percentage are tested through panel data regression to determine their effect on stock price changes in 37 conventional banking companies listed on the Indonesia Stock Exchange from 2018 to 2022. Based on Model Selection Test, the Fixed Effect Model was found to be the most appropriate model for testing. The results of the study conclude that non-performing loans, book to market ratio, earnings per share, and bank size have a negative and significant impact on stock prices. Meanwhile, return on equity, price/earnings to growth ratio, debt to equity ratio, and institutional ownership do not affect stock prices. This study provides a broader overview of the factors influencing stock prices in banking companies listed on the Indonesia Stock Exchange. Therefore, in maximizing their stock prices, banking companies need to pay attention to factors that significantly affect stock prices.